2020
DOI: 10.31149/ijie.v3i3.425
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Curriculum at Kuttab Al-Fatih Surabaya

Abstract: This research describes the concept of the kuttab curriculum during the ancient time and its implementation at the lembaga pendidikan kuttab al-fatih surabaya as part of the national education system. This research is qualified as a special study approach. The data is collected using interview, observation and documents. Whereas in analyzing data it uses the concept of analysis of miles and huberman, which is data reduction, data presentation and making conclusion. This research concludes that: 1. Formerly the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…From the explanation, it can be concluded that the preparation of the KAF curriculum has Sirah Nabawiyah basis, compiled based on the history of the Apostle in preaching and educating friends, taking into account scope and sequence, and arranged thematically in a learning module, namely the nature module, the human module, and the tadabbur module. The KAF curriculum based on the Sirah Nabawiyah is supported by Yudo and Salahuddin (2020). The KAF Education Institute's main goal is to raise an intelligent generation from a young age using a curriculum based on the Sirah that worked well in the past.…”
Section: Kaf Curriculummentioning
confidence: 99%
“…From the explanation, it can be concluded that the preparation of the KAF curriculum has Sirah Nabawiyah basis, compiled based on the history of the Apostle in preaching and educating friends, taking into account scope and sequence, and arranged thematically in a learning module, namely the nature module, the human module, and the tadabbur module. The KAF curriculum based on the Sirah Nabawiyah is supported by Yudo and Salahuddin (2020). The KAF Education Institute's main goal is to raise an intelligent generation from a young age using a curriculum based on the Sirah that worked well in the past.…”
Section: Kaf Curriculummentioning
confidence: 99%